Intrinsically Stretchable and Printable Lithium-Ion Battery for Free-Form Configuration - Hong, Soo Yeong; Jee, Sung min; Ko, Young pyo; Jinhan Cho; KeunHyung Lee; Bongjun Yeom; Kim, Hee suk; Son, Jeong Gon (American Chemical Society, 2022)
For next-generation wearable and implantable devices, energy storage devices should be soft and mechanically deformable and easily printable on any substrate or active devices. Herein, we introduce a fully stretchable lithium-ion battery system for free-form configurations in which all components, including electrodes, current collectors, separators, and encapsulants, are intrinsically stretchable and printable. The stretchable electrode acquires intrinsic stretchability and improved interfacial adhesion with the active materials via a functionalized physically cross-linked organogel as a stretchable binder and separator. Intrinsically stretchable current collectors are fabricated in the form of nanocomposites consisting of a matrix with excellent barrier properties without swelling in organic electrolytes and nanostructure-controlled multimodal conductive fillers. Due to structural and materials freedoms, we successfully fabricate several types of stretchable lithium-ion battery that reliably operates under various stretch deformations with capacity and rate capability comparable with a nonstretchable battery over 2.5 mWh cm